Statins: setting the record straight. Issue 9 (2nd September 2022) - Richardson, Andy
Abstract : Andy Richardson, lecturer in adult nursing, explains how media misrepresentation of statins has impacted patients and the wider public, and what healthcare professionals can do to mitigate this.